How films convey meaning through alternating structures (with an illustrative analysis of The Sunbeam) - Schmidt, Karl-Heinrich (Frontiers in Communication, 2024)
Films and texts differ in terms of their possible logical structures and freedom of presentation on an output medium. While texts can be structured at any depth, the capabilities for structuring films are generally limited. In the presentation of textual documents, the sentence order is usually preserved, whereas video documents often allow rearrangements that lead to new alternations of shots.The fundamental difference between textual and video structures is taken as a starting point. Then, on the basis of a detailed analysis of two different layouts of the film The Sunbeam by D. W. Griffith, a formal criterion for distinguishing between internal, discursively motivated and external, diegetically motivated alternations is developed.The results enable a new approach to alternation in film analysis and production.